Privacy Stress And Brand Trust Implication on Continuous Online Buying Intention - Irfan Hassandi; Mira Gustiana Pangestu; Yosi Fadillah (Jurnal Informatika Ekonomi Bisnis, 2025)
This study investigates how psychological and trust-related factors influence continuous online buying intention among consumers in Jambi City, Indonesia. The research integrates perceived internet risk, consumer self-efficacy, and platform trust as exogenous variables, with privacy stress and brand trust serving as mediating constructs. A quantitative research design was applied, and data were collected through an online survey of 384 active e-commerce users in Jambi. The dataset was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine both direct and indirect relationships among variables. The results show that perceived internet risk significantly increases privacy stress but does not directly diminish brand trust. Consumer self-efficacy and platform trust positively influence brand trust, although neither directly reduces privacy stress. Brand trust emerges as the most influential factor in shaping continuous online buying intention, whereas privacy stress shows no significant direct effect. However, both mediators privacy stress and brand trust play significant indirect roles, transmitting the influence of risk perception, digital confidence, and platform credibility toward behavioral loyalty. The model demonstrates substantial explanatory power, confirming its robustness and predictive validity. Overall, the findings highlight that sustained online purchasing behavior in Jambi’s digital market depends not only on technological reliability but also on emotional assurance and brand credibility. Strengthening consumer trust and reducing psychological discomfort are therefore essential strategies for ensuring long-term digital loyalty.